On the sharpshooter genus Yunga Melichar, 1924 (Hemiptera: Cicadellidae: Cicadellinae): descriptions of a new species from Panama and of the internal female terminalia of Y. cartwrighti Young, 1968 and Y. coriacea Stål, 1864 - Sauceda-V., Jefferson; Takiya, Daniela M. (Zootaxa, 2023)
Yunga Melichar, 1924, is a little-known genus that currently includes three valid species distributed in North America (Mexico), Central America (Costa Rica, Panama), and northern South America (Colombia). A new species of this genus, Y. andresi sp. nov., is described and illustrated based on a single male specimen collected in Bocas del Toro province, Panama. This species can be distinguished from other species of the genus by the following combination of features: (1) apex of style curved inwards, hook-like; (2) aedeagal shaft with paired basal dorsolateral processes, spine-like and short, not extending beyond gonopore; (3) dorsoapical process robust, hook-shaped in lateral view, ending curved and acute; and 4) paraphyses paired, each robust and trifurcate with rami of unequal sizes and thickness. The female genitalia of Y. cartwrighti Young, 1968 and Y. coriacea Stål, 1864 are described and illustrated for the first time. Finally, a distribution map for the species of Yunga, as well as an updated key to species identification, are provided.